Teacher Performance and Learning Achievement on Educational Facilities of High School Students - Yusran Yusran (Universitas Pendidikan Mandalika, 2022)
The purpose of this study was to examine the Professional Development of Teachers, Competencies, Educational Facilities and Infrastructure on Teacher Performance and Learning Achievement of High School Students. The population in this study were all teachers from 5 public high schools and 5 private high schools in the education unit of the Makassar City Education and Culture Office, sample of 183 teachers. The analytical model used in this research is descriptive quantitative and Structural Equation Model (SEM) using the AMOS program. The results showed that teacher professional development had a positive and insignificant effect on teacher performance. Competence has a positive and significant effect on teacher performance. Educational facilities and infrastructure have a positive and significant effect on performance. Teacher professional development has a positive and insignificant effect on student achievement. Competence has a positive but not significant effect on teacher performance. Educational facilities and infrastructure have a positive and significant effect on student learning achievement. Teacher performance has a positive and significant effect on student achievement. Teacher professional development has a positive and significant effect on student learning achievement through teacher performance. Competence has a positive and significant effect on student achievement through teacher performance. Educational facilities and infrastructure have a positive and significant effect on learning achievement of high school students in Makassar City through teacher performance.